THE THE IMPLEMENTATION OF THE CANING LAW IN ACEH: IS IT MORE EFFECTIVE? - Muhibbuthabary; Taslim HM Yasin; Saifuddin A. Rasyid; Rahmad Syah Putra; Rahmat Kurniawan (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2023)
The birth of the caning law in Aceh certainly aims to regulate the life order of the people in Aceh both in terms of behaviour and social aspects so that it is achieved well and is safe and prosperous based on Islamic teachings and norms. This article will briefly describe the effectiveness of applying the caning law in Aceh after enacting the Aceh Qanun Number 6 of 2014 concerning Jinayat Law. This research is qualitative with an anthropological approach using ethnographic methods with data collection techniques using three kinds of methods: in-depth interviews, observation, and documentation. In contrast, data analysis uses four stages: data reduction, data organization, data verification, and conclusion. The research results show that the implementation of caning has not been able to reduce violations of Islamic law, especially in several regions. This is proven by increased cases recorded at the Aceh Sharia Court. The current ineffectiveness of caning is also influenced by the financial aspect, namely the very large budget for the caning procession activities, which is borne by the District/City Regional Governments in Aceh through the District/City Revenue Expenditure Budget (APBK) with a nominal value of one caning procession being quite large. So that it is necessary to redesign the implementation of caning in Aceh practically and economically by referring to the opinion of the Shafi'i school of fiqh, which states that the execution of caning punishment is sufficient to be witnessed by four believers, the procession of caning punishment can be carried out in a simple place, and it is enough to be witnessed by law enforcement officials to minimize budget spending so that it is more effective and efficient. Abstrak: Lahirnya hukum cambuk di Aceh tentunya bertujuan untuk mengatur tatananan hidup masyarakat di Aceh baik dalam aspek tingkah laku maupun aspek sosial agar tercapai dengan baik dan aman sejahtera berdasarkan ajaran dan norma-norma Islam. Artikel ini akan memaparkan secara singkat tentang efektifitas penerapan hukum cambuk di Aceh pasca pemberlakuan Qanun Aceh Nomor 6 Tahun 2014 tentang Hukum Jinayat. Penelitian ini merupakan penelitian kualitatif dengan pendekatan antropologis menggunakan metode etnografi dengan teknik pengumpulan data menggunakan tiga macam cara yaitu wawancara mendalam, observasi dan dokumentasi, sedangkan analisis data menggunakan empat tahapan yaitu: reduksi data, pengorganisasian data, verifikasi data, dan penarikan kesimpulan. Berdasarkan hasil penelitian menunjukkan bahwa Pelaksanaan hukum cambuk belum mampu menurunkan kasus pelanggaran syariat Islam terutama di beberapa daerah. Hal ini terbukti dengan meningkatnya kasus yang tercatat pada Mahkamah Syari’iyah Aceh. Belum efektifnya cambuk dilaksanakan saat ini juga dipengaruhi oleh aspek finansial yaitu anggaran yang sangat besar untuk kegiatan prosesi hukuman cambuk yang dibebankan kepada Pemerintah Daerah Kabupaten/Kota di Aceh melalui Anggaran Pendapatan Belanja Kabupaten/Kota (APBK) dengan nominal satu kegiatan prosesi cambuk berjumlah cukup besar sehingga perlu adanya redesain pelaksanaan cambuk di Aceh secara praktis dan ekonomis dengan merujuk kepada pendapat fiqh Mazhab Syafi’i yang menyatakan bahwa eksekusi hukuman cambuk cukup disaksikan oleh empat orang mukmin. Prosesi hukuman cambuk dapat dilaksanakan pada tempat sederhana dan cukup disaksikan oleh aparatur penegak hukum dengan tujuan untuk meminimalisir pengeluaran anggaran agar lebih efetif dan efisien. Kata Kunci: Efektifitas, Hukum Cambuk, Qanun Aceh, Hukum Jinayat.